DYNAMICS OF INDICATORS OF GENERAL PHYSICAL TRAINING OF 13-15 YEAR-OLD GOALKEEPERS WORKING IN FOOTBALL SCHOOLS (International journal of artificial intelligence, 2025)
The goalkeeper's body's working capacity must be at its maximum level or demonstrate various modes of muscle activity Over time, more and more attention is paid to the presence of general physical qualities. At the same time, attention is required to develop a number of other qualities of a football player.